Laboratory Scale Modeling of Short Transmission Lines Based on 150 kV Line Parameters Using DIgSILENT PowerFactory Simulation - Restu Bramantya Pratomi; Candra Febri Nugraha; Raditya Jayeswara (Electrical Engineering, Universitas Mercu Buana, 2026)
The power transmission system plays a crucial role in distributing energy from power plants to loads; however, its complex technical characteristics often make it difficult to study directly in the field. To address this limitation, this research aims to design and build a 150 kV short-circuit transmission line network system simulator spanning 50 km on a laboratory scale using a scaled-down approach. The method used consists of two main stages. First, simulations of single-line and two-line parallel systems under balanced and unbalanced conditions were conducted using DIgSILENT PowerFactory software to obtain technical parameter data such as transmitter voltage, receiver voltage, and current. Second, the simulation results were used as the basis for designing an electronic simulator based on Proteus 8 Professional that can functionally represent the behavior of the transmission system at a low scale of 380 V. The analysis results show that the two-parallel-line configuration can reduce power losses and maintain voltage stability better than a single-line configuration. Additionally, the developed simulator can safely and effectively visualize system characteristics for educational purposes. The conclusion of this study is that the simulator successfully represents the short-circuit power transmission system and serves as an educational tool in power system learning practices, particularly in understanding system parameters and voltage and current phenomena directly in a laboratory environment.